Extortion [videorecording (DVD)] - Volken, Phil; Bailey, Eion; Abdi, Barkhad; Lenz, Joie, 1981- (Lions Gate Entertainment, 2017)
At a Caribbean resort, Kevin Riley and his family take a carefree boat ride that turns tragic when they're stranded on an island. Near death, they're rescued by a local fisherman who demands a million dollars, then vanishes. Riley must race to find his dying wife and son on an unknown island before their time runs out.